IMPACT OF SEASONALITY OF GENERATION AND LOAD ON THE OPTIMAL CAPACITY OF THE ENERGY STORAGE SYSTEM OF THE PROSUMER’S MICROGRID - O.В. Кулапін; A.В. Івахнов; С.O. Федорчук; К.В. Махотіло; Д.О. Данильченко; О.В. Булгаков (Технічна електродинаміка)
Due to the instability of renewable energy sources, maintaining the stable operation of microgrids becomes an urgent and difficult task. energy storage systems can provide uninterrupted power for such Microgrids, but their integration is accompanied by challenges related to determining the optimal storage parameters. This study presents a method that allows optimizing the capacity of the energy storage system, taking into account various controller algorithms of the operation of the prosumer’s microgrid. Purpose. Development of a method for determining the optimal capacity of an energy storage system to maximize profit from interaction prosumer’s microgrid with the power grid. Two radically different controller algorithms of microgrid operation are considered: the first is focused on the maximum use of solar generation, and the second is on the balanced use of all elements of the prosumer’s microgrid system, including storage and energy consumption. A microgrid was studied using the example of a prosumer, which includes a solar photovoltaic system, a load profile, an energy storage system and connection to the power grid at a three-zone time-to-use tariff. In order to evaluate the effectiveness of the selected strategies, an analysis of indicators for winter and summer days was carried out, which made it possible to reveal the effect of seasonality on the operation of the microgrid. The proposed method allows to determine the capacity of the energy storage system when designing individual solar photovoltaic system. References 15, table 2, figures 10.